Effect of Dietary Inclusion of Papaya Peel Powder on Serum and Carcass Parameters of Japanese Quails.: - A, Sushma; kallam, Nagaraja kumari; D. Narendra nath; P.Kavitha (Indian Journal of Animal Nutrition, 2023)
The present study was carried out to assess the effect of dietary inclusion of Papaya Peel Powder (PPP) on serum biochemical and carcass parametes of J. quails. Day old Japanese quails (N=150) were distributed randomly to five dietary groups each with three replicates of 10 birds and were maintained under uniform management conditions. Experimental diets were prepared with inclusion of PPP at 0, 1.5, 3.0, 4.5 and 6.0 percent in T1, T2, T3, T4 and T5, respectively and were fed for a period of 0-5 weeks. At the end of the fifth week, blood was collected from two birds per replicate a total of 30 samples for serum analysis. At the end of the trial two birds per replicate were slaughtered and carcass traits were studied. The serum biochemical profile of quails revealed that there was significant increase (P